Chemistry at the service of medicine - De Clercq, Erik (Nakladatelství Jihočeské univerzity v Českých Budějovicích, 2021)
The publication focuses on pharmaceutical chemistry and on various drugs. Written for professional public.
Natura
Keywords: farmacie a farmakologie; klinická chemie; farmaceutická chemie; léčivé přípravky; chemie, klinická chemie; Chemistry, Clinical; Chemistry, Pharmaceutical; Pharmaceutical Preparations; biochemie